Effect of low pH on early life stages of the decapod crustacean, Dungeness crab (Cancer magister) - Miller, Jason James (2015)
Thesis (Master's)--University of Washington, 2015 Dungeness crab (Cancer magister) eggs and larvae were exposed to laboratorycontrolled, low-pH seawater in an effort to assess current and predicted-future impacts of Ocean Acidification (OA) on hatching success, survival and growth. Treatment levels of pH ~8.0, ~7.5 and ~7.1 represented the wide range of pH-levels relevant to current-open-ocean, currentupwelled and future-upwelled conditions associated with C. magister habitat in the northeast Pacific Ocean. For this study, pH ~8.0 represented the "control". C. magister eggs were exposed to treatment levels for 34 days. There was no effect of treatment on probability of hatching, however there was a delay in hatch-timing for eggs in pH 7.1. Newly hatched C. magister larvae were exposed to treatment levels for 45 days with 57.9%, 13.5%, and 21.1% surviving in pH 8.0, 7.5, and 7.1 respectively. Larvae in the low-pH treatments were 2.5-3 times less likely to survive than in the control. There was no effect of treatment on larval size at a particular larval stage, however, larvae in the low-pH treatments progressed through larval stages at a slower rate than the control. While some larvae survived the low-pH conditions to the end of the experiment, the lowest survivorship occurred in seawater reflective of pH-levels that can currently be experienced in estuaries and areas of upwelling. The results of this study indicate that low-pH seawater caused by OA can slow down progression through early life stages and that long-duration exposure can result in mortality.